Visualizing Transparent 2D Sheets by Fluorescence Quenching Microscopy. Issue 3 (12th February 2020) - Kong, Zhizhi; Daab, Matthias; Yano, Hitomi; Huang, Haiyue; Breu, Josef; Sasaki, Takayoshi; Nguyen, SonBinh T.; Huang, Jiaxing
Abstract: The high‐contrast optical imaging of nearly transparent 2D materials such as clays and some oxide sheets has been an outstanding challenge; yet there is a critical research capability needed in the synthesis and processing of these materials, which show promise in a number of applications including barrier coatings, membranes, and composites. Using delaminated silicate clay and titania sheets as model systems, here it is shown that these weakly quenching, nearly transparent 2D sheets can be readily imaged by fluorescence quenching microscopy (FQM) based on a new mechanism. When these sheets are deposited on strongly quenching substrates, including doped silicon wafers and metals or indium tin oxide‐coated glass slides, they can act as a "spacer" to reduce the degree of quenching of the dye layer by the substrate, appearing as highly visible bright sheets against a dark background. This new FQM strategy can visualize dielectric 2D materials with high contrast and layer resolutions comparable to scanning electron microscopy and atomic force microscopy. When different 2D materials are co‐deposited, FQM not only differentiates them readily based on their quenching capabilities, but also can resolve their vertical stacking sequence based on the contrast of their overlapped areas. Abstract : Nearly transparent 2D sheets such as clays and oxides can be readily imaged by fluorescence quenching microscopy (FQM) on strongly quenching substrates, such as Si wafers, and metal or ITO‐coated glass slides. FQM can produce high imaging contrast, resolve the number of layers, and even the stacking sequence of different 2D sheets.